Modern Trends in Survey of forest Resources for Industries - Seth, V. K. (Indian Forester, 1972)
The paper deals with the question of surveys of forest resources for industries. For a proper knowledge of the forest resources of a country, region or an industrial catchment, it is necessary to assess reasonably accurately the volume of the existing growing stock and other connected indices such as increment, drain, accessibility, etc. All these are obtained through forest resources surveys. The survey methodology and techniques which have been developed in several countries have been described, and the role of aerial photography and photo-interpretation in modern surveys has been highlighted. There is much to commend in the inclusion of a provision in the Canadian Forest Act for carrying out provincial inventories and the allocation of Federal assistance for this purpose. The Swedish and Finnish National Forest Surveys could serve as useful models, and the concept of a "continuous inventory" on a national scale, which has been developed in them, could constitute the ideal to aim at. Nevertheless, keeping the financial considerations and technological stage of development of a country in mind, it would be necessary to tailor the surveys to provide the required data and answers. The use that is made in Sweden and more especially in Finland of forest Inventory data for formulating silvicultural, management and industrial plans, shows what an important role such resource surveys can play. The MERA development plan for Finland could serve as a good illustration. The idea of financing a resource survey in Mexico by a Bank is worthy of emulation by developing countries. This would generate a healthy developmental trend and provide the much needed capital for formulating regional development plans based on resource survey. Wood-based industries, especially those of pulp and paper, are capital-intensive items and it would be appropriate for any country to decide to invest say at least one per cent of the projected outlay on resource surveys of the areas from where raw materials are to be obtained.